A produção audiovisual no ensino fundamental: uma aposta na autoria e coautoria dos estudantes - Saccol, Lilian Roberta Ilha (2018)
This study, associated with the research’s line Development of Educational Technologies in Network, from the Post-Graduation Program of Educational Technologies in Network, Professional Masters of Federal University of Santa Maria, started from the following research problem: In what way does the audiovisual production made in school space enables students’ authorship and co-authoring processes through the educational technologies in network? The research had as its main goal to understand in what way the audiovisual productions promote students’ authorship and co-authoring, through the educational technologies in network, on the first years of elementary school. Specifically, it was sought to: 1) analyse the usage of educational technologies in network for the elementary school students’ learning process; 2) verify students’ authorship and co-authoring through audiovisual production in school; 3) point out the way that the learning process mediated by the use of educational technologies in network improves a learning process that starts from the students’ authorship and co-authoring. Resultant of this, the masters’ research product consists in a video collection that promoted students’ authorship and co-authoring processes by the usage of educational technologies in network on elementary school. The theoretical framework brings information related to educational technologies in network, audiovisual production in the school space, students’ authorship and co-authoring. The proposed methodology was exploratory and qualitative study, following the action research delineation. The participant observation and the self-evaluation questionnaire were chosen as the data production instruments in this study which had the target audience eight students of the fifth year of elementary school. The research was developed through pedagogical proposals interlaced with educational technologies in network, specially audiovisual production. The delineation used considers that there is a flexibility between the researchers’ action and the researched group, on the various stages of the research. In this way, the study was organised in cycles, each one with the stages of planning, acting, observing and reflecting about the processing and successively coming up with new actions from the reflection of the previous cycle. The content analysis was adopted for the data interpretation, pointing out the existence of four analysis categories, which are: educational technologies in network; authorship and co-authoring; audiovisual production in school; and learning/unlearning processes. As a result, the students showed themselves as authors and co-authors of their learning process, from the audiovisual production creation process.